Kesadaran Hukum di Kalangan Anak Muda Pada Kasus 17 ABG di Bogor Diamankan Saat Hendak Tawuran - M, Mulyadi; Purba, Moses Frederick; Sahwahita, Putri Nabila; Quratuainniza, Happy Sturaya; Desrina, Rania Adriane; Syahreza, Rasya Radella; Novita, Zahra Ersyah; Syahrendra, Muhammad Regan; Putra, Alfarel Endito; Tobing, Ruben Nicholas Alfredo (Media Hukum Indonesia (MHI), 2024)
The development and maturation of a child includes various physical, cognitive, social, and emotional aspects that are influenced by social events that continue to occur and have an influence on increasing the child's thinking and behavior. If not given enough attention in the process of growth and development, children can commit deviant behavior that is not in accordance with the norms, such as the brawl carried out by 17 ABG in Bogor that violated the law. The existence of this concept raises the question of whether there is a relationship between legal awareness and the acts of brawls committed by the 17 children and whether strengthening cooperation between law enforcement agencies and schools can increase students' legal awareness. The purpose of this paper is to examine and analyze the relationship between legal awareness with brawls and steps to increase legal awareness in students. The method used is normative juridical by examining legislation, textbooks, and articles related to the legal issues raised. The results obtained are that there is a relationship between legal awareness and the acts of brawls committed, namely adolescents who lack awareness of the law tend to commit juvenile delinquency and cooperation between law enforcement agencies and schools can increase adolescent legal awareness through socialization to learn the laws that exist in everyday life.